New Nonlinear Conditions and Inequalities for the Existence of Coincidence Points and Fixed Points - Wei-Shih Du; Shao-Xuan Zheng (Journal of Applied Mathematics)
Some new fixed point theorems for nonlinear maps are established. By using these results, we can obtain some new coincidence point theorems. Our results are quite different in the literature and references therein.